Improvements of Football Clubs’ Marketing Strategies in Russian Reality (Laisvalaikio tyrimai, 2021)
Relevance and novelty. The article examines the issues related to the marketing activities of Russian football clubs in order to identify patterns in this process, as well as assessing the prospects for an integrated approach to evaluating such strategies in modern conditions, in particular, solving the issue of maximizing the effectiveness or efficiency and increasing the attractiveness of Russian football clubs in the international arena.Justification for the study. Therefore, it is the actions of specific specialists that largely determine how exactly a football club positions itself in the external environment, and also with the help of which tools it solves the problems of increasing the brand’s popularity and attracting fans to stadiums, which directly contribute to the increase in sales of related products to clubs. Marketing management in a football club as well as in companies of other industries should be based on a marketing strategy that should solve a number of specific issues and ensure that the football club is stable in the external environment even in times of crisis. In this regard, the relevance of theoretical and practical research of this problem cannot be questionable.The purpose of this study was to investigate how Russian football clubs deal with marketing activities in the new reality and consider the ways of optimizing their work.Methods. The main research methods were literary review, analysis and synthesis of information, modeling and statistical analysis.Results. As a result of the work, it was concluded that a marketing strategy is necessary for every football club, since it can be used not only to generate new ways of interacting with stakeholders, but also to create a good idea of the brand and ensure its promotion with much lower costs and problems. and also evaluate the effectiveness of brand communications. Realizing that organizational efficiency and effectiveness to a large extent depends not only on titles won, but also on financial performance, fan base growth, as well as the number of followers in social networks, which then turn into loyal fans, we can conclude that for a correct and adequate assessment of the club's marketing strategy and its overall activities requires a system that will consider these, as well as unnamed, but no less important, indicators.Conclusion. Based on the research, it is necessary to understand that the marketing strategy of a football club can significantly facilitate its task of increasing material well-being, as well as provide audience growth in the stands and brand recognition not only in the territory of a particular country, but also beyond its borders.Keywords: football, marketing, integrated approach.